Assessment on the Occurrence of Anisakid and other Endoparasitic Nematodes Infecting Commercially-Important Fishes at Tayabas Bay - Ramos, Maribeth H.; Argarin, Trazarah Hanoof E.; Olaivar, Beatriz A. (2020)
Anisakid nematodes are parasites commonly present in the marine environment. Parasites belonging to the family Anisakidae or the genus Anisakis can cause two different clinical manifestations: gastrointestinal disorders and allergic reactions known as anisakiasis. In this study, we examined 7,126 marine fishes belonging to four different commercially-important fish species; Rastrelliger kanagurta, Sardinella lemuru, Atule mate, and Selar crumenophthalmus for the presence of anisakid and other endoparasitic nematode infection. The fishes caught from Tayabas Bay were bought from three different landing sites from March 2017 to February 2018. The gonads, liver, and stomach of each fish species were incubated for 12-18 hours for rapid isolation and endoparasite evaluation. After the isolation of parasites, anisakid nematodes were fixed in vials with 70% ethanol for morphological analysis under the microscope. Six anisakid groups of genera, including Hysterothylacium, Terranova, Anisakis, Contracaecum, Raphidascaris, and Camallanus, and a non-anisakid group Echinorhynchus were identified. The results showed that the prevalence of anisakid infection in all species was 24.18 %, with a mean intensity of infection of 1.91. Rastrelliger kanagurta (Dalahican), Atule mate, and Selar crumenophthalmus were the most infected with 50.90%, 38.98%, and 30.52% prevalence rate, respectively, followed by Rastrelliger kanagurta (San Francisco) (24.18%) and Sardinella lemuru (7.46%). The collected data suggest that commercially-important fish caught in the Tayabas Bay waters are susceptible to parasitization by larvae of the genus Camallanus followed by Hysterothylacium and Terranova in their visceral organs. The prevalence of anisakid infection was almost similar between female (45.3 %) and male (47.21 %) fishes with a mean intensity of 1.95 & 1.96, respectively. Also, larger fishes were heavily infected with anisakid larvae than small fishes. Thus, the intensity and prevalence of the fish parasite can be used as a biological tag ...